Foraging of psilocybe basidiocarps by the leafcutting ant acromyrmex lobicornis in Santa Fé, Argentina - Masiulionis, Virginia E. [UNESP]; Weber, Roland W. S.; Pagnocca, Fernando C. [UNESP] (Springer Nature, 2013)
Background It is generally accepted that material collected by leaf-cutting ants of the genus Acromyrmex consists solely of plant matter, which is used in the nest as substrate for a symbiotic fungus providing nutrition to the ants. There is only one previous report of any leaf-cutting ant foraging directly on fungal basidiocarps. Findings Basidiocarps of Psilocybe coprophila growing on cow dung were actively collected by workers of Acromyrmex lobicornis in Santa Fé province, Argentina. During this behaviour the ants displayed typical signals of recognition and continuously recruited other foragers to the task. Basidiocarps of different stages of maturity were being transported into the nest by particular groups of workers, while other workers collected plant material. Conclusions The collection of mature basidiocarps with viable spores by leaf-cutting ants in nature adds substance to theories relating to the origin of fungiculture in these highly specialized social insects. © 2013 Masiulionis et al.
Keywords: Acromyrmex lobicornis; Basidiocarps; Coprophilous fungus; Deconica coprophila; Forage behaviour; Leaf-cutting ants; Psilocybe coprophila